Co-administration of combretastatin A4 nanoparticles and sorafenib for systemic therapy of hepatocellular carcinoma. (1st July 2019) - Wang, Yalin; Yu, Haiyang; Zhang, Dawei; Wang, Guanyi; Song, Wantong; Liu, Yingmin; Ma, Sheng; Tang, Zhaohui; Liu, Ziling; Sakurai, Kazuo; Chen, Xuesi
Graphical abstract: Abstract: Effective systemic therapy is highly desired for the treatment of hepatocellular carcinoma (HCC). In this study, a combination of nanoparticles of poly(L-glutamic acid)- graft -methoxy poly(ethylene glycol)/combretastatin A4 sodium salt (CA4-NPs) plus sorafenib is developed for the cooperative systemic treatment of HCC. The CA4-NPs leads to the disruption of established tumor blood vessels and extensive tumor necrosis, however, inducing increased expression of VEGF-A and angiogenesis. Sorafenib reduces the VEGF-A induced angiogenesis and further inhibits tumor proliferation, cooperating with the CA4-NPs. A significant decrease in tumor volume and prolonged survival time are observed in the combination group of CA4-NPs plus sorafenib compared with CA4-NPs or sorafenib monotherapy in subcutaneous and orthotopic H22 hepatic tumor models. Seventy-one percent of the mice are alive without residual tumor at 96 days post tumor inoculation for the subcutaneous models treated with CA4-NPs 30 or 35 mg·kg −1 plus sorafenib 30 mg·kg −1 . Our findings suggest that co-administration of sorafenib and CA4-NPs possesses significant antitumor efficacy for HCC treatment. Statement of Significance: Effective systemic therapy is highly desired for the treatment of hepatocellular carcinoma (HCC). Herein, we demonstrate that a combination of nanoparticles of poly(L-glutamic acid)- graft -methoxy poly(ethylene glycol)/combretastatin A4 sodium salt (CA4-NPs) plus sorafenib is a promising synergistic approach for systemic treatment of HCC. The CA4-NPs leads to the disruption of established tumor blood vessels and extensive tumor necrosis, however, inducing increased expression of VEGF-A and angiogenesis. Sorafenib reduces the VEGF-A induced angiogenesis and further inhibits tumor proliferation, cooperating with the CA4-NPs.